Hepatitis A Profile: Epidemiological, Clinical and Outcomes in Children’s Welfare Teaching Hospital and the Need for Hepatitis A Vaccine Programme Setting - Theajeal, Rabab F.; Al hadeethi, Bandar M.; Jasim, AlZahraa Sh.; Abdullah, Batool K. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Hepatitis A virus, a single-stranded RNA virus from the family Picornaviridae, is primarily transmitted via the fecal-oral route. The World Health Organization reports about 1.5 million hepatitis A cases annually, with the incidence rates closely linked to socioeconomic conditions. This vaccine-preventable disease is the focus of our research. Objectives: The current research aimed to elucidate the incidence, clinical presentation, and outcomes of hepatitis A in Iraq, highlighting the importance of appropriate preventive measures. Methods: It wasconducted as a retrospective cohort study from January 2019 to July 10, 2022, and a prospective cohort study from July 11, 2022, to September 30, 2022. A total of 238 confirmed HAV cases 189 retrospective and 49 prospective were analyzed. Data included demographic characteristics, clinical presentations, laboratory findings, and ultrasonographic results. HAV IgM positivity was confirmed using the MAGLUMI HAV IgM Chemiluminescent Immunoassay CLIA). Results: Most cases were observed in the 6 to 10-year-old age group p=0). Gender distribution was nearly equal, with males at 50.8% and females at 49.2%. Clinical profiles included jaundice 96.2%), hepatomegaly 45.4%), abdominal distention 15.6%), splenomegaly 7%), and bleeding 5.9%). Ultrasound findings showed an enlarged liver 45.4%), thickened edematous gallbladder wall 31.2%), enlarged spleen 14.9%), and ascites 4.2%). Biochemical analysis revealed mean values of SGPT 786.8 U/l), SGOT 647.6 U/l), TSB 10.34 mg/dl), Alb 3.9 g/dl), PT 14.9 sec), PTT 36.45 sec), and INR 1.15). Severe cases were 8 in number, with acute liver failure 4 deaths) and 6 with hepatic encephalopathy 5 deaths), and a mortality rate of 2.1% of which the male-to-female ratio was 4:1. Conclusion: This study underscores the need for vaccine implementation to prevent and control HAV infection in Iraq, given the high incidence and ongoing risks.